Jai Bhim Comrade and the Politics of Sound in Urban Indian Visual Culture. Issue 2 (November 2014) - Matzner, Deborah
<x xml:space="preserve">Abstract</x> Indian documentary filmmaker Anand Patwardhan's latest release Jai Bhim Comrade (2012), which depicts protest music employed by the Dalit (previously "Untouchable") movement in Maharashtra, presents challenges to the ways in which Patwardhan's work has been characterized. Key among these are the sonic practices in which Dalits in the film engage to assert presence and agency in defiance of their caste subjugation. Situating these practices in the everyday sonic ecologies of Indian cities, I think through the importance of sound to the study of South Asian visual culture and documentary, and interrogate the primacy of the visual in scholarship on visual culture.